Comparative study on the antileishmanial activities of chemically and biologically synthesized silver nanoparticles (AgNPs) - Ullah, Ikram; Cosar, Gizem; Abamor, Emrah Sefik; Bagirova, Melahat; Shinwari, Zabta Khan; Allahverdiyev, Adil M. (SPRINGER HEIDELBERG, 2018)
The present study was conducted to investigate the antileishmanial activity of biogenic silver nanoparticles (AgNPs) compared to chemically synthesized AgNPs. A nano dimension size (10-15 nm) biogenic AgNPs was produced and characterized by UV-Vis spectroscopy and X-rays diffraction. The chemically synthesized AgNPs was recovering from our previous study with a nanoparticle (NP) size in the range of 10-40 nm. The antileishmanial activities were investigated through 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide cell viability assay. The infectivity was determined by Giemsa staining of the infected macrophages cells. Nitric oxide (NO) accumulation was measured by Griess reagent using NaNO2 as a positive control. After 24 h of exposure with nanoparticles (NPs), a concentration-dependent growth inhibition was observed. The IC50 values were determined against promastigotes of L. infantum as 19.42 +/- 2.76 mu g/ml for leaves aqueous extract mediated AgNPs, 30.71 +/- 1.91 mu g/ml for stem mediated AgNPs and 51.23 +/- 2.20 mu g/ml for chemically synthesized AgNPs. It was also detected that all types of NPs produced NO at a significant level. However, the production of a high-level of NO in the biologically synthesized NPs activated macrophage cells, infected with L. infantum promastigotes indicates that NO radicals are mainly responsible for induced cell death and a decrease in the pathogenicity of the parasites. Since, biogenic nanoparticles are cost-effective, eco-friendly, simple to synthesize, and more effective than chemically synthesized silver nanoparticles, therefore, it could be used as a potential alternative for the development of antileishmanial drugs.
Keywords: Biological synthesis; Silver nanoparticles; XRD; Teucrium stocksianum Boiss.; Antileishmanial activities; Infectivity; NITRIC-OXIDE; TEUCRIUM-STOCKSIANUM; LEISHMANIA PARASITES; EXTRACT; MACROPHAGES; VACCINES; Biotechnology & Applied Microbiology